Group Identity, Performance Transparency, and Employee Performance - Shang, Ruidi; Abernethy, Margaret A.; Hung, Chung-Yu (The Accounting Review, 2020)
ABSTRACT Economics, social psychology, and management studies suggest that group identity plays an important role in directing employee behaviors. On the one hand, strong group identity could motivate high effort to resolve conflicts of interests in the workplace. On the other hand, it could encourage conformity toward group norms. We examine whether the effect of group identity is conditional on managers' performance reporting choices. Drawing on survey and archival data from a field site, we find that when performance transparency is low, the interest alignment effect is more salient and group identity positively relates to employee performance. However, when performance transparency is high, the conformity effect is more salient and higher group identity is associated with more homogeneous, but not necessarily higher, employee performance. Our findings contribute to the management control literature by documenting that managers' performance reporting choices determine whether group identity has positive effects on employee performance. Data Availability: Data in this study are derived from a proprietary source.